The association between pancreatic diseases and pancreatic fat content: a cross-sectional study from the UK Biobank - Gao, Jing; Dong, Xiaowu; Shi, Xiaolei; Yang, Yuqing; Chen, Weiwei; Xiao, Weiming; Lu, Guotao; Yu, Xiaoping (Frontiers in Endocrinology, 2025)
ObjectiveMany researches have demonstrated an association between intra-pancreatic fat deposition (IPFD) and several pancreatic pathological conditions, including pancreatitis, pancreatic cancer, and type 2 diabetes mellitus (T2DM). The aim of this study is to investigate the influence of pancreatic diseases on the accumulation of pancreatic fat, to further explore which kind of pancreatic disease is significant, and to find out the possible mediating factors.MethodsA cross-sectional study based on the UK Biobank (UKB) data categorized participants by pancreatic disease status and collated relevant information. IPFD was measured using MRI in combination with a deep learning-based organ segmentation model, nnUNet. Linear regression models and mediation analysis were employed to explore the association between pancreatic diseases and IPFD.ResultsAmong 61,088 participants, those with pancreatic diseases exhibited higher IPFD than those without (pancreatic endocrine diseases: 11.72% vs 7.94%, P<0.001; pancreatic exocrine diseases: 9.44% vs 8.03%, P<0.001). After adjusting for multiple variables, a positive association between pancreatic endocrine diseases (particularly T2DM) and IPFD persisted, but not for pancreatic exocrine diseases. Obesity and dyslipidemia partially explained the relationship between T2DM and IPFD.ConclusionPancreatic exocrine disorders are not associated with an increased risk of IPFD, whereas pancreatic endocrine disorders, particularly T2DM, may exhibit a positive relationship. However, the possibility of reverse causation cannot be discounted.